2018
DOI: 10.5204/ssj.v9i3.463
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the first-year experience of a non-traditional student: A case study

Abstract: This article concerns non-traditional students’ involvement in Australian higher education. It aims to deepen understanding of enabling and constraining factors for this group’s retention, through an in-depth case study of a non-traditional student’s university experience. The study is underpinned by principles of phenomenology, hermeneutics and idiography with data analysis involving an inductive coding process and a thematic analysis. Findings draw attention to the need to provide support for non-traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This finding is consistent with numerous research studies that have reported the transition challenges new university students encounter. Kearney et al (2018) reported that first-year students encountered challenges interpreting nontraditional students' first-year experiences. Javed (2020) reported that first-year students experience difficulty adapting to the university environment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with numerous research studies that have reported the transition challenges new university students encounter. Kearney et al (2018) reported that first-year students encountered challenges interpreting nontraditional students' first-year experiences. Javed (2020) reported that first-year students experience difficulty adapting to the university environment.…”
Section: Discussionmentioning
confidence: 99%
“…There are various approaches to retention that have been suggested including advocating practical applications of theory and enlisting peer mentor programmes to support first-year students (Davis and Taylor 2019). Other actions advocated include academic skills support, first-year advisors and programmes promoting a strong sense of community (Kearney et al 2018).…”
Section: First-year University Experiencementioning
confidence: 99%
“…In short 'we have gone from a higher education system that serves only a narrow band of people, to a broader, more diverse and more open system' (BIS, 2016, p.7). Whilst in many ways these changes have been welcomed as broadening education to include more people, it also created challenges for establishments whose support networks could not cope with the increased numbers and the diversity of students (Kearney, Stanley and Blackberry, 2018). Support networks within UK universities have traditionally focused on making sure that there was someone on hand to provide academic and emotional support for students (Lusk and Fearful, 2014).…”
Section: Changing He Landscapementioning
confidence: 99%